Secondary metabolite profiling of plant pathogenic Alternaria species by matrix assisted laser desorption ionization–time of flight (MALDI-TOF) mass spectrometry - and RIAZ MAHMOOD, M. JYOTHI LAKSHMI, P. CHOWDAPPA* (Indian Phytopathology, 2014)
Profiling of secondary metabolite production (both known and unknown metabolites) on standardized culture media has proven to be useful for classification and identification of certain morphologically similar species of Alternaria. In this study, secondary metabolite profiling of 50 fungal isolates belonging to 10 plant pathogenic Alternaria species such as A. solani, A. porri, A. brassicicola, A. brassicae, A. sesame, A. alternata, A. macrospora, A. ricini, A. carthami and A. brunsii isolated from vegetable, oil yielding and seed spice crops were examined. Secondary metabolites were extracted from 14 day old cultures, grown on potato dextrose agar, with ethyl acetate containing formic acid. After extraction, the secondary metabolite profiles of all fungal isolates were analyzed using thin layer chromatography (TLC), high performance liquid chromatography (HPLC) and matrix assisted laser desorption ionization–time of flight (MALDI-TOF) mass spectrometry. These analyses indicated characteristic ‘species-specific metabolite finger prints’. Thus, chemotaxonomic approach is a simple and rapid technique to determine the chemical diversity of the different Alternaria species and to identify species specific metabolites that could be adopted as chemotaxonomic markers in species identification. This study can be integrated in a polyphasic approach.